Torque and Drag Analysis for Horizontal Extended Reach Coiled Tubing Drilling - Alezzi, Mustafa M.; Khader, Ali; Kader, Aiham S. (Iraqi Journal of Chemical and Petroleum Engineering, 2024)
One of the major elements faced in downhole drilling operations of oil and gas wells is the limited reach of coiled tubing (CT) in horizontal wellbores. To address this issue, this work creates an extended reach limit simulation of CT with starting bending curvature in a horizontal wellbore for an Iraqi well in the Ahdeb oil field. Using Drillbench software, a calculation approach is provided based on contact force and buckling models to determine the extended reach limit of CT. The findings of this study have significant implications for improving downhole drilling engineering design parameters and predicting the extended reach limit of CT. By considering factors such as friction resistance and contact force between the wellbore, a more accurate assessment of the CT’s abilities can be suggested based on well trajectory curvature and well devotion. To achieve this, a slim open hole with a diameter of 6 inches was drilled to a measured depth ranging from 3755 to 3986.5 m. The results showed that a consistent trend in azimuth and inclination in the completed section, with the hook load increasing by about 25 tons during pickup and decreasing by 11.4 tons during slack-off along the curved section due to friction effect. Additionally, elongation and relative stress showed slight increase during pickup in curved areas due to friction and temperature effect, while values decreased during slack-off due to drag action. Pressure loss in the curved section was found to be lower compared to the vertical section, primarily due to the bit nozzle discharge effect. Eventually, the friction coefficient values remained within acceptable industry limits. Ultimately, the study determined limited extended lengths for CT in this horizontal well.